The Effect of Locally Delivered Doxycycline in the Treatment of Chronic Periodontitis. A Clinical and Microbiological Cohort Study - Ioannis Ioannou; Nikolaos Dimitriadis; Konstantinos Papadimitriou; Ioannis Vouros; Dimitra Sakellari; Antonis Konstantinidis (eJournal of Oral Maxillofacial Research)
Objectives: To evaluate the efficacy of locally delivered doxycycline as an adjunct to non-surgical treatment with the use of an ultrasonic device compared to scaling and root planing using hand instruments, by means of clinical and microbiological criteria.Material and Methods: Thirty three patients with chronic periodontitis participated in this cohort study and were divided into two groups. Patients in control group received scaling and root planing using hand instruments, whereas patients in control group received ultrasonic debridement and 8.8% doxycycline gel was applied after initial therapy and at 3 months at preselected sites. Clinical recordings concerning probing pocket depth, clinical attachment level, plaque index and gingival bleeding index were performed at baseline, 3 and 6 months after baseline. Subgingival samples were analysed using the “checkerboard” DNA-DNA hybridisation technique for Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola.Results: Both treatments resulted in significant improvement in all clinical recordings. Six months after the treatment a statistically significant decrease was observed for Porphyromonas gingivalis in both of groups and Treponema denticola in the control group (P < 0.05). No inter-group differences were observed (P < 0.05).Conclusions: Both treatment modalities provided comparable clinical and microbiological results in the treatment of chronic periodontitis.